The U.S. Constitution And Constitutional Law - Brian Duignan
Although one of the shortest written constitutions in the world, the U.S. Constitution, designed to embody the rights, laws, and guiding principles of a diverse and ever-changing populace, remains an enduring document. Since its ratification in 1787, the Constitution has been applied to a broad range of legal and political questions and, while often the subject of much debate, continues to serve as a stalwart reminder of the country$1 (Bs social and legal strides. This detailed volume breaks down each section of the Constitution and its amendments, also providing a concise overview of the field of constitutional law as it is applied around the world and in various forms of government.s